Preservation of learning outside the primary classroom: A comparison of policy and practice in Danish udeskole (outdoor school) and English primary Outdoor Education (OE) - Megan McGee; Joe Gazdula; Elliott Gazdula (Educational Futures, 2022)
This opinion piece advocates the benefits of incorporating Outdoor Education (OE) into primary education practice across the curriculum by evaluating OE policies and practices in Denmark and England. Using a literature-based auto-ethnographic informed approach we look at the benefits gained through participating in outdoor primary education in Danish folkskoler (weekly schools) which practise udeskoler (outdoor schools) and compare these with English primary schools. By outlining the different OE policies in each country, the barriers encountered, and the different teaching practices used, we evaluate the effectiveness of the respective policies and approaches. Our conclusions are that there is more freedom for teachers to practise and explore creative Outdoor Education approaches in udeskoler and, while the overall policies towards OE in the two countries are similar, differences in practice occur due to the different ways the respective education systems apply their respective policies. In England the National Curriculum enforced by Ofsted inspections places OE as a subset of Physical Education (PE) which narrows its use in the broader curriculum. In Denmark, the management of schools through local school boards and parent participation in decision-making allows teachers a different perception of risk, facilitates more experimentation and better integration of a wider curriculum in udeskoler.